What is known about neuroplacentology in fetal growth restriction and in preterm infants: A narrative review of literature - Gardella, Barbara; Dominoni, Mattia; Scatigno, Annachiara Licia; Cesari, Stefania; Fiandrino, Giacomo; Orcesi, Simona; Spinillo, Arsenio (Frontiers in Endocrinology, 2022)
The placenta plays a fundamental role during pregnancy for fetal growth and development. A suboptimal placental function may result in severe consequences during the infant's first years of life. In recent years, a new field known as neuroplacentology has emerged and it focuses on the role of the placenta in fetal and neonatal brain development. Because of the limited data, our aim was to provide a narrative review of the most recent knowledge about the relation between placental lesions and fetal and newborn neurological development. Papers published online from 2000 until February 2022 were taken into consideration and particular attention was given to articles in which placental lesions were related to neonatal morbidity and short-term and long-term neurological outcome. Most research regarding the role of placental lesions in neurodevelopment has been conducted on fetal growth restriction and preterm infants. Principal neurological outcomes investigated were periventricular leukomalacia, intraventricular hemorrhages, neonatal encephalopathy and autism spectrum disorder. No consequences in motor development were found. All the considered studies agree about the crucial role played by placenta in fetal and neonatal neurological development and outcome. However, the causal mechanisms remain largely unknown. Knowledge on the pathophysiological mechanisms and on placenta-related risks for neurological problems may provide clues for early interventions aiming to improve neurological outcomes, especially among pediatricians and child psychiatrists.